PENGUATAN LITERASI SEBAGAI UPAYA PENGEMBANGAN SUMBER DAYA MANUSIA DESA WONOKROMO LAMONGAN - Sutikno; Siti Musarofah; Yanuangga Galahatlambang; Eli Indira; Mochammad Kholilurrahman (JURNAL PENGABDIAN MASYARAKAT AKADEMISI, 2023)
Literacy learning has the main goal of providing opportunities or opportunities for the community to develop themselves. The purpose of this service is a form of effort to develop human resources (HR) in Wonorejo Village. The subjects of service in the field of educational literacy are the students of SDN 1 Wonokromo and the subjects of service in the field of religion are the children of the Wonorejo Hamlet TPQ. the implementation of this service, the team uses the cooperative learning method. The participants were very enthusiastic and enthusiastic in participating in every activity in this learning. They really pay close attention to every explanation given. A pleasant learning atmosphere is able to encourage participants in literacy.